In vitro antiurolithic effect of Siddha drugs with and without adjuvant on oxalate stones - Liyanawadugel, R.M.; Sivagnanam, S.; Arasaratnam, V. (University of Jaffna, 2020)
Siddha drugs are indicated for the management of urolithiasis and coconut water is used as the adjuvant in indigenous medicine. This study was carried out to evaluate the in vitro antiurolithic effects of Siddha drugs Silasaththu paspam, Nandukkal paspam and Venkara paspam with coconut water as the adjuvant) on oxalate stones collected by the Department of Biochemistry, Faculty of Medicine, University of Jaffna. Methods: This is a laboratory-based experimental study design. Constituents in the Siddha drugs, adjuvant (coconut water, and their mixtures were analysed for calcium, magnesium, oxalate, uric acid, inorganic phosphate and citrate. For the in vitro antiurolithic activity evaluation, the oxalale stones were treated three times with each Siddha drug, adjuvant (coconut water) and their mixtures. Deionized water with the stone was used as the control. The solutions were decanted after 24 hours and fresh solutions were added into cach tube. Soluble ions in every solution were calculated each day for 6 consecutive days.
Keywords: Antiurolithic; Coconut Water; Oxalate Stone; Siddha Drugs